2015
DOI: 10.1002/dmrr.2650
|View full text |Cite
|
Sign up to set email alerts
|

Blood group AB is protective factor for gestational diabetes mellitus: a prospective population‐based study in Tianjin, China

Abstract: Blood group AB was a protective factor against GDM in pregnant Chinese women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 39 publications
2
20
1
6
Order By: Relevance
“…Sidhu et al [12] has increased association of blood group AB with diabetis mellitus. Wherever decreased association of blood group AB with diabetis mellitus found in study of Buckwalter, [13] Zhang et al [14] Our study has increased association of blood group O with DM. This results are similar with Karagoz et al, [9] Zhang et al, [14] and dissimilar with Kamil et al, [15] Fagherazzi et al [16] Bener and Yousafzai, [17] Qureshi and Bhati.…”
Section: Discussionsupporting
confidence: 48%
“…Sidhu et al [12] has increased association of blood group AB with diabetis mellitus. Wherever decreased association of blood group AB with diabetis mellitus found in study of Buckwalter, [13] Zhang et al [14] Our study has increased association of blood group O with DM. This results are similar with Karagoz et al, [9] Zhang et al, [14] and dissimilar with Kamil et al, [15] Fagherazzi et al [16] Bener and Yousafzai, [17] Qureshi and Bhati.…”
Section: Discussionsupporting
confidence: 48%
“…According to previous reports, the incidence of many diseases was related to blood groups. [ 13 15 ] The study by Ramesh which was conducted at various cancer hospitals in Kanpur and found that people with blood group A and AB had a lower risk of oral cancer than people with others. [ 16 ] The Wolpin study found that people with blood group A, B, or AB had a higher risk of developing pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…En el estudio de Shimodaira, otra población oriental mostró que tanto el grupo o como A y b eran protectores de DG comparados con el grupo Ab 9 , lo que se contradice parcialmente con nuestro estudio, donde la presencia del antígeno b aparece como protector. En otro estudio en 14.198 embarazadas con DG según criterio de la International Association of Diabetes and Pregnancy Study Group, Zhang encontró que los grupos A, b y o estaban más asociados a DG que el grupo Ab 8 , hallazgo completamente opuesto al de Shimodaira. Diferencias genéticas en población japonesa, en comparación a la china, así como factores culturales, podrían dar cuenta de las contradicciones entre los estudios de grupo Abo en estas poblaciones y justifican estudiar distintas poblaciones junto con posibles factores confundentes e interacciones que puedan dar cuenta de la verdadera asociación entre DM2/DG y grupo Abo.…”
Section: Discussionunclassified
“…Por otro lado, la diabetes gestacional, definida como cualquier grado de intolerancia a la glucosa reconocida por primera vez durante el embarazo, es una enfermedad de alta incidencia en nuestro país, que se relaciona a un pronóstico adverso, tanto para la madre como para el feto. Si bien algunos autores han promovido el tamizaje universal de DG, otros sugieren la pesquisa basada en factores de riesgo 8 , de manera de controlar los costos y minimizar los falsos positivos.…”
unclassified
See 1 more Smart Citation